Pengaruh Pemasaran Media Sosial Dan Persepsi Calon Mahasiswa Terhadap Keputusan Pemilihan Perguruan Tinggi: Studi Kasus Pada Institut Teknologi Del (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the impact of social media marketing strategies and prospective students' perceptions on their decision-making process in choosing an educational institution. The research employs a quantitative approach. Data was collected through questionnaires distributed to 50 purposively selected respondents, specifically prospective students considering Institut Teknologi Del as their higher education option. Multiple linear regression analysis was used to process the collected data, examining the causal relationship between the independent variables (social media marketing and perception) and the dependent variable (college selection decision).The findings indicate that effective social media marketing strategies and positive perceptions among prospective students significantly influence their decision to choose a higher education institution. The results reveal that improving the quality and reach of social media marketing, as well as fostering positive perceptions about the institution—such as academic quality, facilities, and graduate career prospects—can increase prospective students' interest in selecting Institut Teknologi Del as their place of study.